2017
DOI: 10.1186/s12913-017-2172-9
|View full text |Cite
|
Sign up to set email alerts
|

Patients who restart antiretroviral medication after interruption remain at high risk of unfavorable outcomes in Ethiopia

Abstract: BackgroundAchieving optimal adherence to highly active antiretroviral therapy (HAART) is necessary to attain viral suppression and hence optimal clinical outcome. Interruptions in antiretroviral therapy medication often occur, but a substantial proportion restart treatment. Long-term care engagement practices and clinical outcomes have not been described among cohorts of individuals on HAART in Ethiopia.MethodsIn this study we describe treatment interruption patterns over time among clients who interrupt and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
5
11
0
Order By: Relevance
“…A systematic review of individual and contextual factors affecting retention and adherence among pregnant and post-partum women living with HIV found that religious beliefs and use of alternative medicines discouraged ART adherence [16]. Similar findings have been reported from other studies involving different populations [1719]. Other systematic reviews of barriers to ART adherence in developing and developed countries showed that the fear to disclose HIV status, treatment suspicion together with the desire to avoid taking medication in public places among others, negatively affected adherence [20, 21].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…A systematic review of individual and contextual factors affecting retention and adherence among pregnant and post-partum women living with HIV found that religious beliefs and use of alternative medicines discouraged ART adherence [16]. Similar findings have been reported from other studies involving different populations [1719]. Other systematic reviews of barriers to ART adherence in developing and developed countries showed that the fear to disclose HIV status, treatment suspicion together with the desire to avoid taking medication in public places among others, negatively affected adherence [20, 21].…”
Section: Introductionsupporting
confidence: 71%
“…There are contrasting reports on the association between duration on ART and adherence. Whereas some studies have reported decreasing adherence with increasing duration on ART [2, 14, 17, 21, 2831], others have reported an increase in adherence as people stay longer on ART [29, 3236].…”
Section: Introductionmentioning
confidence: 99%
“…We also found that ART interruption during TB treatment increased the risk of unfavourable TB treatment outcome. Literature shows that ART interruptions are associated with a decrease in CD4 cell count, increase in viral load and development of opportunistic infections [22,23]. Even though TB meningitis was a rare event in our cohort, it was significantly associated with an increased risk of unfavourable TB treatment outcome and death.…”
Section: Articlementioning
confidence: 64%
“…Retention measures are also limited as they are generally calculated retrospectively: data sources poorly distinguish between the loss to follow‐up and death [ 158 ] and often miss “silent transfers” between different facilities [ 158 ]. This can be addressed by following patients to evaluate alternate outcomes and adjust estimates: either through tracing a sample [ 57 ], using weights from the literature [ 27 , 134 ] or using national/combined databases to follow patients who move between facilities [ 3 , 158 ]. However, all these approaches increase the burden of data collection, linkage and analysis, reducing their feasibility in practice.…”
Section: Resultsmentioning
confidence: 99%